Effect Of Service Quality And Promotion On Consumer Loyalty Mediated By Consumer Satisfaction Among ShopeePay Users On The Shopee E-Commerce Platform - Dimas Archadea Junaedi; Nur Efendi; Diang Adistya (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to examine the influence of service quality and promotion on customer loyalty, mediated by customer satisfaction among ShopeePay users on the Shopee e-commerce platform. The background of this research is based on the decline of ShopeePay's ranking as the most recommended digital wallet in 2023. Methodology: This research adopts a quantitative approach using an explanatory research method. The sample consists of 385 active ShopeePay users, collected through an online questionnaire. Data analysis was conducted using SmartPLS software. Results: The results indicate that both service quality and promotion have a positive and significant effect on customer satisfaction, and customer satisfaction positively and significantly affects customer loyalty Findings: These findings suggest that improving service quality and implementing effective promotional strategies can enhance customer satisfaction and loyalty toward ShopeePay. Novelty: This research contributes to marketing by focusing on the quality of service and promotion of ShopeePay users in Indonesia, on Shopee e-commerce. Originality: This research is original and focuses on the use of ShopeePay in Indonesia, particularly in relation to the Shopee e-commerce platform. Conclusion: This study recommends prioritizing effective ShopeeCare and Home Care service quality to ensure consumers experience security and convenience when transacting using ShopeePay. The study also recommends effective promotional strategies to maintain customer satisfaction and loyalty to ShopeePay. Type of Paper: research papers